Guidelines for the use of imaging in the management of patients with myeloma. (5th July 2017) - Chantry, Andrew; Kazmi, Majid; Barrington, Sally; Goh, Vicky; Mulholland, Nicola; Streetly, Matthew; Lai, Maggie; Pratt, Guy; ,
Summary: The role of imaging in myeloma has gained increasing importance over the past few years. The recently revised definition of myeloma from the International Myeloma Working Group (IMWG) includes cross sectional imaging as a method to define bone disease and also incorporates its use in the disease definition for patients with suspected smouldering myeloma. The National Institute for Health and Care Excellence myeloma guidelines also recommend cross sectional imaging for patients with suspected myeloma. There is also increasing use of imaging in disease assessments and the International Myeloma Working Group has recently incorporated imaging in defining new response categories of minimal residual disease negativity, with or without imaging‐based evidence of disease. Plain X‐rays have previously been the standard imaging modality included in a myeloma work up at presentation but evidence is mounting for use of cross‐sectional modalities such as computed tomography (CT), magnetic resonance imaging (MRI) and 18 fluoro‐deoxyglucose ( 18 F‐FDG) positron emission tomography (PET)/CT. Funding and therefore availability of newer imaging techniques remains a barrier. Here, we propose an evidence‐based approach to the use and technical application of the latest imaging modalities at diagnosis and in the follow‐up of patients with myeloma and plasmacytoma.